Urban Road Transportation Externalities : Costs and Choice of Policy Instruments - Timilsina, Govinda R. (World Bank, 2013)
Urban transportation externalities are a key development challenge. Based on the existing literature, the authors illustrate the magnitudes of various external costs, review response policies, and measure and discuss their selection, particularly focusing on the context of developing countries. They find that regulatory policy instruments aimed at reducing local air pollution have been introduced in most countries in the world. On the other hand, fiscal policy instruments aimed at reducing congestion or greenhouse gas emissions are limited mainly to industrialized economies. Although traditional fiscal instruments, such as fuel taxes and subsidies, are normally introduced for other purposes, they can also help to reduce externalities. Land-use or urban planning, and infrastructure investment, could also contribute to reducing externalities; but they are expensive and play a small role in already developed megacities. The main factors that influence the choice of policy instruments include economic efficiency, equity, country or city specific priority, and institutional capacity for implementation. Multiple policy options need to be used simultaneously to reduce effectively the different externalities arising from urban road transportation because most policy options are not mutually exclusive.